2015
DOI: 10.1007/s11682-015-9483-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral changes and cognitive impairment after an ischemic heart disease: a multimodal MRI study

Abstract: Three to 6 months after an acute coronary syndrome (ACS), cognitive impairment is observed in more than 30 % of the patients, mainly in executive functioning. The aim of this study was to investigate, using multimodal MRI, cerebral anatomo-functional substratum of executive dysfunction. Thirty-three patients were recruited 4 ± 1 months after a first ACS. Executive functions were evaluated with the Trail-Making-Test-B (TMTB) at baseline (ie 4 ± 1 months after ACS) and 6 months later (ie 10 ± 1 months after ACS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…23 These alterations are related to an increased functional connectivity in prefrontal regions. 12 Memory, especially verbal memory, 20 is another domain frequently implied in coronary disease. A recent animal study showed that after myocardial ischemia, reperfusion leads to reactive gliosis in hippocampal subregions CA1, CA3 and dentate gyrus, thus suggesting an inflammatory basis for the memory deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 These alterations are related to an increased functional connectivity in prefrontal regions. 12 Memory, especially verbal memory, 20 is another domain frequently implied in coronary disease. A recent animal study showed that after myocardial ischemia, reperfusion leads to reactive gliosis in hippocampal subregions CA1, CA3 and dentate gyrus, thus suggesting an inflammatory basis for the memory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…11 The executive dysfunction in these patients is associated with an increased functional connectivity in middle-orbito-frontal regions. 12 …”
Section: Introductionmentioning
confidence: 99%
“…9 It is theorised that vascular changes, similar to those noted in the heart during ACS, cause silent infarcts in the brain leading to CI. 10,11 Changes in connectivity intensity, presence of white matter and grey matter atrophy have also been noted in the middle orbito-frontal region following ACS. 11 These changes may lead to CI as the middle orbito-frontal regions are the key areas of the brain that perform cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Changes in connectivity intensity, presence of white matter and grey matter atrophy have also been noted in the middle orbito-frontal region following ACS. 11 These changes may lead to CI as the middle orbito-frontal regions are the key areas of the brain that perform cognitive tasks. 11 Additionally, other factors arising from the ACS diagnosis and hospitalisation, such as depression and anxiety, are likely to contribute further to CI in the early recovery stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation